Social media exposure to health misinformation and effect on vaccination intention and behaviour - Zaifuddin, Nur Syaheera; Adzharuddin, Nor Azura; Osman, Mohd Nizam; Mohd Zawawi, Julia Wirza (Human Resources Management Academic Research Society (HRMARS), 2024)
The proliferation of health misinformation on social media has raised significant public health concerns, particularly regarding its influence on vaccination intentions and behaviors. This study investigates the relationship between exposure to health misinformation on social media platforms and the subsequent effects on individuals' intentions to vaccinate and their actual vaccination behaviors. Utilizing a mixed-methods approach, we combine quantitative survey data with qualitative interviews to provide a comprehensive understanding of this phenomenon. Our findings suggest that increased exposure to health misinformation on social media correlates with higher levels of vaccine hesitancy and a decrease in vaccination rates. The study underscores the need for targeted interventions to combat misinformation and promote accurate health information on social media.